KEMAMPUAN MENGIDENTIFIKASI UNSUR INSTRINSIK NASKAH DRAMA MENGGUNAKAN TEKNIK INKUIRI SISWA KELAS VIII MTs TI BATANG KABUNG KOTA PADANG - Marlina, Leni; Bahardur, Iswadi; Ramadansyah, Ramadansyah (Pendidikan Bahasa Indonesia, 2014)
This research is motivated by the lack of student interest in identifying the intrinsic elements of a play. The purpose of this study was to describe the ability to identify intrinsic element plays eighth graders MTs TI Batang Kabung Padang of City. This research is a quantitative research using descriptive methods. The population in this study is the eighth grade students of MTs TI Batang Kabung Padang numbering 110 people. The sampling technique used is proportional random sampling which amount to 32 people. The results showed that the ability of eighth graders MTs TI Batang Kabung Padang of City identify intrinsic elements of the drama script by using the technique of inquiry are the qualifications Good (B) with an average value of 76 is in the range 76-85. Picture of students ability to identify the elements intrinsic drama script as follows: (1) the ability of students to identify elements of the theme are the qualifications More than Enough (LC). (2) the ability of students to identify elements of the mandate is at qualifying Both (B). (3) the ability of students to identify the elements that are in the qualification Good (B). (4) The ability of students to identify the elements that are in the qualifying groove More Than Enough (LC). (5) The ability of students to identify the elements that are in the background plays qualifier More Than Enough (LC).Â